INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Damayanti, Alvina; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of Intellectual Capital on firm value through profitability as an intervening variable. This research was conducted on pharmaceutical companies listed on the Indonesia Stock Exchange. This study used a sample of 6 pharmaceutical companies with a five-year period during 2016-2020 which were selected by purposive sampling technique. The collection technique was obtained through the IDX's official website: www.idx.co.id. Data analysis and hypothesis testing in this study used the Structural Equation-Partial Least Square (PLS-SEM) method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Intellectual capital has a significant negative effect on Profitability, Intellectual capital has a significant positive effect on Firm Value, Profitability is negative but not significant to Firm Value, and Intellectual Capital has a positive but not significant effect on Firm Value through Profitability.